Financial Bookkeeping Training With Microsoft Excell For Chicken Farming UMKM In Parepare - Wahrini, Retyana; Hasbi, Hasbi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
Making simple financial reports based on Microsoft Excel to manage business processes for the micro, small and medium industrial world is very much needed for the business progress of Chicken Farming UMKM. Currently, many Microsoft Excel-based bookkeeping systems that are simple and easy to understand have been created with the aim of helping micro, small and medium enterprises (UMKM) obtain efficient, fast and accurate business reports. The problem that arises is that these UMKM business actors are not used to using a Microsoft Excel-based bookkeeping system, which makes the performance of these UMKM business unit players less good. This training activity was attended by several chicken farming business people in the city of Parepare. The activity ran smoothly and the participants were very enthusiastic. Aya Farms UMKM players are expected to improve their skills in compiling quality financial reporting data using Microsoft Excel.